2021
DOI: 10.2139/ssrn.3847450
|View full text |Cite
|
Sign up to set email alerts
|

Governance and renewable energy consumption in sub-Saharan Africa

Abstract: The purpose of this study is to assess the nexus between governance and renewable energy consumption in sub-Saharan Africa. The focus is on 44 countries in Sub-Saharan Africa with data from 1996 to 2016. The empirical evidence is based on Tobit regressions. It is apparent from the findings that political and institutional governance are negatively related to the consumption of renewable energy in the sampled countries. The unexpected findings are clarified and policy implications are discussed in the light of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
3
5
0
Order By: Relevance
“…This study, therefore, invites future perception-based studies to test the questionnaire items used in this study as depicted in Table 2. This study did not test whether energy consumption mediates the relationship between energy governance and sustainable development practices and yet, there are studies such as those of Asongu and Odhiambo (2021) which indicate that energy governance and energy consumption are related. Future studies may, therefore, investigate whether energy consumption mediates the relationship between energy governance and sustainable development practices.…”
Section: Conclusion and Areas For Further Researchmentioning
confidence: 92%
See 4 more Smart Citations
“…This study, therefore, invites future perception-based studies to test the questionnaire items used in this study as depicted in Table 2. This study did not test whether energy consumption mediates the relationship between energy governance and sustainable development practices and yet, there are studies such as those of Asongu and Odhiambo (2021) which indicate that energy governance and energy consumption are related. Future studies may, therefore, investigate whether energy consumption mediates the relationship between energy governance and sustainable development practices.…”
Section: Conclusion and Areas For Further Researchmentioning
confidence: 92%
“…Energy governance involves the quality of NGQ attributed to market reforms and institutional settings, energy policy and legislation and information disclosures; PLS which relates to political acceptance and controlled corruption; and integration into international governance (ING) which is attributed to assistance from international development and external influences in energy policy (Zaman and Brudermann, 2017). Energy governance has been linked to energy consumption (Asongu and Odhiambo, 2021). Asongu and Odhiambo (2021) found that political and institutional governance are negatively associated with energy consumption in 44 countries found in Sub-Saharan Africa.…”
Section: Energy Governance Mechanisms and Sustainable Development Pra...mentioning
confidence: 99%
See 3 more Smart Citations